2018
DOI: 10.1111/bjd.15879
|View full text |Cite
|
Sign up to set email alerts
|

Sebocytes contribute to skin inflammation by promoting the differentiation of T helper 17 cells

Abstract: Our study provides evidence that human sebocytes actively participate in inflammatory processes in the skin by recruiting and communicating with immune cells. This interaction leads to the generation of Th17 cells, which might contribute to the pathogenesis not only of acne vulgaris, but also of several inflammatory skin diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 41 publications
(51 reference statements)
2
56
0
Order By: Relevance
“…In conclusion, our previous and present data suggest that not only the microbiota and chemical content of human skin show three main topographical areas (dry, moist, oily/ sebaceous), but probably in correlation to this, the immune and barrier characteristics of these topographical regions are also distinct, which can make these skin regions become prone to the development of "region-specific" inflammatory skin diseases, like HS on AGR and acne (Mattii et al, 2018) and rosacea (Dajnoki et al, 2017) on sebaceous glandrich areas.…”
supporting
confidence: 49%
“…In conclusion, our previous and present data suggest that not only the microbiota and chemical content of human skin show three main topographical areas (dry, moist, oily/ sebaceous), but probably in correlation to this, the immune and barrier characteristics of these topographical regions are also distinct, which can make these skin regions become prone to the development of "region-specific" inflammatory skin diseases, like HS on AGR and acne (Mattii et al, 2018) and rosacea (Dajnoki et al, 2017) on sebaceous glandrich areas.…”
supporting
confidence: 49%
“…We found that noncytotoxic concentrations of VDM11 and AM404 (see Supplementary Figures S3, S4a, and S7) induced a moderate but significant increase in SLP (Figure 3a, and see Supplementary Figure S4b) and that VDM11 interfered with the proinflammatory effects of LPS (Figure 3b and c). Certain sebocyte-derived cytokines (e.g., IL-6) can induce differentiation of CD4 þ /CD45RA þ naïve T cells into T helper type 17 cells (Mattii et al, 2017), further supporting the concept that dysregulation of sebocyte biology can contribute not only to the development of acne, but also to other (partly) T helper type 17-driven inflammatory dermatoses, such as AD or psoriasis. Thus, the suppression of IL-6 expression and release that we have shown here (Figure 3b and c) is likely to be clinically relevant and promises to be beneficial in such conditions.…”
Section: Discussionmentioning
confidence: 59%
“…Keratinocytes elicit and maintain the skin immune response through the secretion of soluble factors, including cytokines, as well as antimicrobial peptides (Nagy et al, 2005). Sebocytes in follicles colonized with C. acnes have shown increased cyclooxygenase-II (COX-II) expression (Makrantonaki et al, 2011;Mattii et al, 2018). The production of excess PGE 2 results in sebaceous gland enlargement and increased sebum production, favoring C. acnes proliferation (Ottaviani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%